Exploring the mechanical, tribological, and morphological characteristics of areca fiber epoxy composites reinforced with various fillers for multifaceted applications - Miniappan, P. K.; Marimuthu, S.; Dharani Kumar, S.; Sharma, Shubham; Kumar, Abhinav; Salah, Bashir; Ullah, Syed Sajid (Frontiers in Materials, 2023)
This investigation is primarily concerned with the effect of fly ash, basalt powder, and tungsten carbide (WC) on the mechanical, microstructural, and tribological behaviour of areca fiber-reinforced composites. The fillers (5-10 wt. %) were included with the areca fiber epoxy reinforced composites. In comparison to areca fiber composites without fillers, the inclusion of fly ash, basalt powder, and WC increased the tensile strength by 33–48.2 MPa. The tensile strength of an A2 composite containing areca fiber (20wt. %), epoxy (70 wt. %) and basalt powder (10 wt. %) was measured to be 48.2 MPa. Similarly, filler incorporation enhanced flexural, impact, and Shore D hardness properties by up to 21.25%, 13.18 %, and 15.66%, respectively. Furthermore, the hybridization of fillers enhanced the mechanical properties and abrasion resistance of areca fiber reinforced composites. The inclusion of filler increases the load-carrying capability and adhesion, as determined by SEM. The river-like pattern demonstrates that ductile failure was dominated in the A5 (areca fiber (20 wt. %), epoxy (70 wt. %), fly ash (5 wt. %) and basalt powder (5 wt. %)) composites. A4 (areca fiber (20 wt. %), epoxy (70 wt. %), fly ash (5 wt. %) and tungsten carbide (5 wt. %)) composite has a lower wear resistance than all other composites. The hybrid filler-reinforced composite exhibits increased wear resistance as a result of the absence of wear detritus and textured surfaces.